Effect of age on visual acuity after cataract extraction. Issue 2 (February 1987) - Jay, J L; Mammo, R B; Allan, D
Abstract : The best Snellen visual acuity in the three months after cataract extraction was found to decline with the age of the patient. The relationship was identical in 111 patients who had extracapsular extraction and a Pearce tripod posterior chamber intraocular lens and in 50 patients who had intracapsular extraction with spectacle correction. Vision after operation varied from a mean value of 6/5 at 50 years to 6/12 at 90 years, a decline of 1 line per 13.4 years. In the intracapsular group, over a mean follow-up period of 14 years, the rate of fall in acuity with increasing age after operation was found to be statistically similar to that of the early postoperative acuity plotted against age for both types of operation. This suggests that the rate of decline with age is unchanged after a prolonged period of aphakia with presumed increased exposure to ultraviolet and blue light. The data were found to be similar to the decline in the neurosensory elements of vision with age measured experimentally in 20 phakic subjects by laser interferometry. This method of assessment of contrast sensitivity threshold effectively bypasses changes in the optical media. The findings indicate that the previously recognised drop in visual acuity with age is not related to changes in the aging crystalline lens and support the view that there is a decline in the neurosensory elements of vision. It is important to recognise this deterioration so that results of surgery or other treatment are adjusted to allow for the age of the patients.